Analisis Keandalan Gardu Induk Teluk Lembu PT. PLN Pekanbaru Dengan Metode Section Technique Menggunakan Software ETAP - Athur Marune C; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Analysis of the level reliability in this study using section technique methods compared with ETAP software. Objectives to be presented in this study provide information about reliability of the Teluk Lembu substation PT. PLN Pekanbaru. By dividing the distribution networks based methods of calculating level of reliability section technique, which impacts the perceived failure of the same componet if the occurrence of the disoders that cause system outages. Step by step execution of this study include collecting data, performing calculations failure parameter, calculating the reliability index SAIDI (System Average Interruption Duration Index) and SAIFI (System Average Interruption Frequency Index). The calculate result obtained by using section technique method SAIFI = 1,745 time/hour, SAIDI = 5,34 hour/year, and CAIDI = 3,06 hour/year. With exiting standard in Indonesia as SPLN 68-2 : 1986 has values SAIFI (System Average Frequency Duration Index) is 3,2 time/hour and SAIDI (System Average Interruption Duration Index) is 21 hour/year, the index reliabilty of the distribution Feeder Surian still in the category reliable.Keywords: Section Technique, reliability, distribution system